Iniciativas e desafios do setor portuário para os ODS 11 e 14 - AZEVEDO, Randolfo Rocha (2023)
The port sector plays a crucial role in both the global and local economy, being responsible for handling a large portion of international trade. As such, ports can be considered essential logistical hubs for the movement of goods and play a pivotal role in connectivity between countries and regions. Given this global economic significance, ports have also become the focus of sustainability improvements, aiming to implement enhancements and actions related to this theme. In this regard, the adoption of the Sustainable Development Goals (SDGs) in the port sector emerges as a guiding tool for achieving sustainability through the targets and indicators of each SDG. Given this importance, it is necessary to understand the progress of SDG implementation in the port sector, as well as to ascertain the actions and challenges of Brazilian ports and terminals in achieving and contributing to SDG 11 and SDG 14. Thus, this study aimed to identify strategies for adopting and implementing the Sustainable Development Goals (SDGs), specifically focusing on SDG 11 (Sustainable Cities and Communities) and SDG 14 (Life Below Water), in the context of the Brazilian port sector. The sample included six respondents for the SDG 11 questionnaire and eight for the SDG 14 questionnaire. The approach of dividing the questionnaires proved effective, allowing for robust data collection for analysis purposes. The results showed significant adherence of actions related to SDG 11 to target 11.4, but relatively low adherence to target 11.6. Regarding sustainability initiatives linked to SDG 14, it was found that these are aligned with targets 14.1, 14.2, and 14.5. Among the identified good sustainability practices, actions focused on interaction between ports and cities, partnerships with educational institutions and government bodies, obtaining ISO 14.001 certification, and implementing environmental monitoring programs stand out. However, opportunities for improvement were identified, involving the enhancement of existing monitoring methods, incorporating new approaches and technologies into the environmental management system. Additionally, it is crucial to pay attention to specific issues, such as air quality, underwater noise emissions, and mangrove protection. The challenges identified include low participation of environmental authorities in sustainability-related initiatives and agendas, high workforce turnover, the absence of specific targets related to the SDGs, and a lack of alignment of environmental policy with the SDG targets. Despite the limitations identified, this study successfully achieved its objective of assessing initiatives and challenges related to SDGs 11 and 14 in the Brazilian port sector. Furthermore, it highlighted the need for future research focused on the critical areas identified.